A Fuzzy based Decision Support System for Agriculture Support System - Varshney, Monika; Shrivastava, Azad Kumar; Aggarwal, Alok (International Journal of Computer Sciences and Engineering, 2018)
A fuzzy logic based decision support system (DSS) for agriculture support system is presented. The primary focus is on the algorithm used to correctly predict how much water should be poured to the agriculture for the optimal growth of the crops. Over-watering as well as under-watering has always been a big problem in farming. The proposed system uses three input parameters; namely field moisture, field humidity and field temperature. However, for predicting the proper amount of water so as to get the optimized best growth of the crop, few more parameters also play a vital role but in this work for simplicity purpose we have taken these three parameters as input. Through decision support system, the meaning of transferred data is translated into linguistic variables that can be understood by non-experts. Mamdani inference engine is used to deduce from the input parameters. Design of the proposed system is given with the fuzzy logic controller and simulation is being done using MATLAB (Matrix Laboratory) for solving the water irrigation issue.